Estimation of Valacyclovir in Tablets and Human Serum by RP-HPLC Method - Raja Rajeswari, K.; Nageswararao, P.; Sankar, G.G.; Rao, A.L.; Raju, D.B.; Rao, J.V.L.N.S. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive and precise reverse phase-high performance liquid chromatographic (HPLC) method has been developed for the estimation of valacyclovir in tablets and human serum. In this method, RP-C18 column (150 x 4.6 mm I.D., 5 μm particle size) with mobile phase consisting of acetonitrile and 0.03 M phosphate buffer pH 2.99 in the ratio of 50 : 50 v/v in isocratic mode was used. The detection wavelength is 230 nm and the flow rate is 0.8 mL/min. In the range of 0.05-8 μg/mL, the linearity of valacyclovir shows a correlation coefficient of 0.9999. The mean recovery of the drug from the spiked serum solution was found to be 97.82%. The proposed method was validated by determining sensitivity, accuracy, precision and system suitability parameters. The high percentage of recovery indicates that there is no interference from the other serum contents.